2015
DOI: 10.3889/oamjms.2015.024
|View full text |Cite
|
Sign up to set email alerts
|

Work Demands-Burnout and Job Engagement-Job Satisfaction Relationships: Teamwork as a Mediator and Moderator

Abstract: BACKGROUND:Few studies have examined teamwork as mediator and moderator of work demands-burnout and job engagement-job satisfaction relationships in healthcare workers (HCWs) in South-East Europe.AIM:To assess mediation and moderation effect of teamwork on the relationship between independent (work demands or job engagement) and dependent (burnout or job satisfaction) variables.METHODS:Work demands, burnout, job engagement, and job satisfaction were measured with Hospital Experience Scale, Maslach Burnout Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 26 publications
(42 reference statements)
1
27
0
2
Order By: Relevance
“…For example, Vahey DC et al registered an average score of emotional exhaustion - 24.3 and an average score of depersonalization - 7.4 in nurses from 40 units in 20 urban hospitals across the United States [ 31 ]. Similarly, low mean values of both burnout dimensions were also registered in HPs in other studies conducted in R. Macedonia [ 29 ][ 30 ][ 32 ][ 33 ]. In a study conducted in HPs from seven South and South - Eastern European countries, adopting a cross-national approach, Macedonian HPs demonstrated levels of emotional exhaustion (EE) and depersonalization (DP) in the lower end of the average EE and DP scores [ 34 ].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…For example, Vahey DC et al registered an average score of emotional exhaustion - 24.3 and an average score of depersonalization - 7.4 in nurses from 40 units in 20 urban hospitals across the United States [ 31 ]. Similarly, low mean values of both burnout dimensions were also registered in HPs in other studies conducted in R. Macedonia [ 29 ][ 30 ][ 32 ][ 33 ]. In a study conducted in HPs from seven South and South - Eastern European countries, adopting a cross-national approach, Macedonian HPs demonstrated levels of emotional exhaustion (EE) and depersonalization (DP) in the lower end of the average EE and DP scores [ 34 ].…”
Section: Discussionsupporting
confidence: 68%
“…Different studies have shown that teamwork predicted lower levels of burnout. The more that HPs experienced teamwork, the less they felt burnt out [ 15 ] [ 17 ] [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Istraživanja u svetu su pokazala da su za osećaj zadovoljstva zdravstvenih radnika poslom značajni mnogobrojni faktori, kao što su: pol, starost, nivo obrazovanja, dužina radnog staža, mesto zaposlenja, novčani iznos mesečne zarade, način organizacije posla, sigurnost zaposlenja, autonomija prilikom obavljanja posla, mogućnost usavršavanja, uslovi rada, podrška od strane nadređenog, radno vreme, kooperativna radna atmosfera, mogućnost napredovanja i slično (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Uvodunclassified
“…Isto istraživanje pokazuje da su medicinske sestre/ tehničari koji imaju mogućnost edukacije (pohađanje seminara i kongresa) zadovoljniji svojim poslom. Studija Mijakoskog i saradnika (13), sprovedena u zdravstvenoj ustanovi u Skoplju, ukazuje da osećaj timskog rada dovodi do većeg zadovoljstva zdravstvenih radnika poslom po pitanju adekvatnosti planiranja rada, radnih uslova, sigurnosti posla, dobijanja pohvala od strane rukovodioca za dobro obavljen posao, podrške na poslu koju im pružaju nadređeni, mogućnosti stručnog usavršavanja, visine finansijske nadoknade za rad i beneficija. Rezultati istraživanja Sindikata doktora medicine Crne Gore pokazuju da interesantan i kreativan posao, dobri odnosi sa rukovodiocima i kolegama na poslu, visoka plata, autonomija prilikom obavljanja posla, mogućnost napredovanja i sigurnost posla predstavljaju najčešće faktore zadovoljstva poslom lekara zaposlenih u zdravstvenim ustanovama u Crnoj Gori (14).…”
Section: Diskusijaunclassified